Three Dimensional Space-Time Analysis Theory of Geotechnical Seismic Engineering - Yang, Changwei; Yang, Guotao; Zhang, Jianjing; Ma, Hongsheng (Springer Nature Singapore : Imprint: Springer, 2019)
Written by respected experts, this book presents essential findings on the Wenchuan earthquake. It establishes a series of time-frequency analysis methods, and subsequently applies them to the layered site, slope, and earth-retaining wall. Further, it examines various cases and their solutions, and shares the results of numerous shaking-table tests and numerical simulations. As such, it is a valuable resource for researchers and engineers in the fields of geotechnical engineering and anti-seismic engineering.